2021
DOI: 10.3390/antiox10030463
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bioavailability of Selenium in Selenium-Enriched Streptococcus thermophilus and Enterococcus faecium in CD IGS Rats

Abstract: The selenium (Se) enrichment of yeasts and lactic acid bacteria (LAB) has recently emerged as a novel concept; the individual health effects of these beneficial microorganisms are combined by supplying the essential micronutrient Se in a more bioavailable and less toxic form. This study investigated the bioavailability of Se in the strains Enterococcus faecium CCDM 922A (EF) and Streptococcus thermophilus CCDM 144 (ST) and their respective Se-enriched forms, SeEF and SeST, in a CD (SD-Sprague Dawley) IGS rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In a study by Wastney et al [152] the enteric absorption of single doses of SeMet by healthy subjects was 98%, indicating the high bioaccessibility of SeMet. Moreover, another investigation demonstrated that the bacterial selenized forms selenocystein (SeCys) and SeMet were also present in the liver and kidney tissues of rats after 58 days under an experimental diet [27]. In a further study, the Se content in the liver of animals fed a diet fortified with Se-enriched Bifidobacterium longum was much higher than that of animals fed a selenite-enriched diet [29].…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 90%
See 3 more Smart Citations
“…In a study by Wastney et al [152] the enteric absorption of single doses of SeMet by healthy subjects was 98%, indicating the high bioaccessibility of SeMet. Moreover, another investigation demonstrated that the bacterial selenized forms selenocystein (SeCys) and SeMet were also present in the liver and kidney tissues of rats after 58 days under an experimental diet [27]. In a further study, the Se content in the liver of animals fed a diet fortified with Se-enriched Bifidobacterium longum was much higher than that of animals fed a selenite-enriched diet [29].…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 90%
“…Bacteria may compete with the host for Se when availability becomes limiting [148], although, in the mouse model, Lactobacillus plantarum enriched with Se and Zn increases antioxidant activity and blood Se levels [135]. In the study of Krausova et al [27], the administration of Se-enriched lactic acid bacteria (Streptococcus thermophilus and Enterococcus faecium) improved the antioxidant status of the rats.…”
Section: Interaction Of Selenium and Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bioavailability of Se on Enterococcus faecium CCDM 922A (EF) and Streptococcus thermophilus CCDM 144 (ST) and their respective forms enriched with Se, SeEF, and SeST, improved their antioxidant status in animal models (151). Selenium works by blocking the activation of nuclear factor-kB through modulation of expression of selenoprotein genes and by inhibiting the production of reactive oxygen species (ROS) (152).…”
Section: Selenium Microbiota and Cardiovascular Diseasesmentioning
confidence: 99%